Does butylphthalide affect on hemodynamics in patients with watershed stroke?: A protocol of systematic review and meta-analysis. Issue 20 (15th May 2020) - Jia, Li-na; Zhang, Ya-juan; Ma, Rong; Song, You
Abstract: Background: This study will specifically investigate the effect of butylphthalide on hemodynamics in patients with watershed stroke (WS). Methods: We will search the following databases from their inceptions to the March 1, 2020: Cochrane Library, MEDLINE, EMBASE, PsycINFO, Web of Science, Cumulative Index to Nursing and Allied Health Literature, and China National Knowledge Infrastructure. All relevant randomized controlled trials on exploring the effect of butylphthalide on hemodynamics in patients with WS will be considered for inclusion. No language limitation will be imposed to this study. All study quality will be checked using Cochrane risk of bias tool. RevMan 5.3 software will be utilized for data analysis. Results: This study will summarize the latest evidence to investigate the effect of butylphthalide on hemodynamics in patients with WS. Conclusion: Findings from this study will provide theoretical basis of butylphthalide on hemodynamics in patients with WS for clinician and future research. Dissemination and ethics: This study is carried out based on the published data, thus, no ethical approval is required. We will submit this study to a peer-reviewed journal for publication. Systematic review registration: INPLASY 202030006.